A Proposed Sylaby for Teaching Literacy to Deaf Students - Suryanti, Yanti (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Curriculum is the guidance for the teachers to carry out their tasks in the teaching and learning process. The content of the curriculum should accommodate the students needs and should be based on their abilities as well. So far, mostly of the English skills in any type of school are taught to the students separately, and they causethe studentscannot integrate the skills. Many previous works have only focused on the curriculum for general school students, hence, the works focus on the curriculum for special needs students in form of D/HH students are a bit neglected. The fruitful of teaching literacy to deaf students cannot be ignored; therefore, deafness should never be excused of hampering on literacy. Literacy is defined as the ability to read, write and furthermore it processes the knowledge to be applied into the written one. Learning to read and write is a part of any language development or process. The paper presents a new approach to integrate the syllabus of two basic competencies in one standard competency for teaching literacy to deaf. By applying the mix methodwith the seven participants and a teacher of a deaf school, the study reveals that the integrated syllabus for both skills could help deaf students understand the two skills taught easily.